An Expert Opinion/Approach: Clinical Presentations, Diagnostic Considerations, and Therapeutic Options for Gastrointestinal Manifestations of Common Variable Immune Deficiency. (November 2022) - Hashash, Jana G.; Squire, Jacqueline; Francis, Fadi F.; Binion, David G.; Cross, Raymond K.; Farraye, Francis A.
Abstract : Common variable immunodeficiency (CVID) is the most common symptomatic primary immunodeficiency. It is characterized by impaired B-cell differentiation. Although patients can be diagnosed with CVID anytime during their lifetime, most patients have symptoms for 5–9 years before their diagnosis. The diagnosis of CVID starts with a detailed history focusing on the infectious and noninfectious manifestations of the disease. In patients who are suspected to experience CVID, quantitative immunoglobulins (Ig) should be checked to confirm the diagnosis. IgG should be at least 2 times less than the age-specific SD along with either a low IgA or IgM and with evidence of impaired vaccine response. CVID is usually associated with infectious and/or noninfectious conditions, the latter of which can be inflammatory, autoimmune, lymphoproliferative, or malignant, among other manifestations. Ig therapy has positively affected the disease course of patients with infectious complications but has limited effect on the noninfectious manifestations because the noninfectious complications are related to immune dysregulation involving B cells and T cells rather than primarily due to antibody deficiency. When the gastrointestinal (GI) system is involved, patients with CVID may display signs and symptoms that mimic several GI conditions such as celiac disease, pernicious anemia, or inflammatory bowel diseases. The inflammatory bowel disease–like condition is usually treated with steroids, 5-aminosalicylates, thiopurines, or biologic agents to control the inflammation. In this review, the clinical presentations, diagnostic considerations, and therapeutic options for GI manifestations of CVID will be discussed to facilitate the individualized management of these often-complex patients.